2013
DOI: 10.5664/jcsm.2410
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and Epilepsy: A Questionnaire-Based Study

Abstract: Study Objectives: Although disturbed sleep has been frequently reported in patients with seizures, little is known about insomnia and epilepsy. The aims of this study were (1) to analyze the prevalence and degree of insomnia in patients with epilepsy, (2) to examine the clinical features and correlates of insomnia in these patients, and (3) to evaluate the impact of poor sleep on their quality of life. Methods: One hundred-fi fty-two patients with epilepsy (mean age 46 years) completed the following questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 40 publications
8
36
2
Order By: Relevance
“…Detrimental and beneficial effects on sleep and wakefulness have been reported; however, prospective, randomized trials investigating these effects are lacking. Polytherapy with AEDs was associated with an increased ISI score in the present study, and this result is comparable with findings from another recent study [30]. Finally, with the exception of evaluating for OSA, we did not analyze whether other primary sleep disorders may have contributed to the insomnia complaint.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Detrimental and beneficial effects on sleep and wakefulness have been reported; however, prospective, randomized trials investigating these effects are lacking. Polytherapy with AEDs was associated with an increased ISI score in the present study, and this result is comparable with findings from another recent study [30]. Finally, with the exception of evaluating for OSA, we did not analyze whether other primary sleep disorders may have contributed to the insomnia complaint.…”
Section: Discussionsupporting
confidence: 93%
“…Vendrame et al found a prevalence of moderate or severe insomnia in 55% of 152 adults with less refractory epilepsy referred to their sleep center [30]. They used the same criteria for moderate or severe insomnia (ISI ≥ 15) but did not exclude patients with preexisting insomnia as we did.…”
Section: Discussionmentioning
confidence: 89%
“…In support of our findings, Parrino et al (2000) reported that nocturnal seizures and interictal activities can lead to arousals and insomnia. More recently, a significant correlation between insomnia and the number of AEDs or scores of depressive symptoms was reported in epilepsy patients (Vendrame et al, 2013). In contrast, there was no correlation between the presence of insomnia and type/numbers of AEDs or depression in our patients.…”
Section: Tablecontrasting
confidence: 45%
“…Patients with different types of epilepsy may experience either daytime sleepiness or nighttime sleep disturbance [36]. The prevalence of sleep disorders, such as excessive daytime sleepiness [7, 8], insomnia [9, 10] and obstructive sleep apnea [8, 10] is higher among patients with epilepsy.…”
Section: Introductionmentioning
confidence: 99%